Quality assessment of videos on social media platforms related to gestational diabetes mellitus in China: A cross-section study - Qin-Yu Cai; Jing Tang; Si-Zhe Meng; Yi Sun; Xia Lan; Tai-Hang Liu (Heliyon, 2024)
Purpose: This study aimed to systematically evaluate the quality of content and information in videos related to gestational diabetes mellitus on Chinese social media platforms. Methods: The videos on various platforms, TikTok, Bilibili, and Weibo, were searched with the keyword “gestational diabetes mellitus'' in Chinese, and the first 50 videos with a comprehensive ranking on each platform were included for subsequent analysis. Characteristic information of video was collected, such as their duration, number of days online, number of likes, comments, and number of shares. DISCREN, JAMA (The Journal of the American Medical Association) Benchmark Criteria, and GQS (Global Quality Scores) were used to assess the quality of all videos. Finally, the correlation analysis was performed among video features, video sources, DISCERN scores, and JAMA scores. Results: Ultimately, 135 videos were included in this study. The mean DISCERN total score was 31.84 ± 7.85, the mean JAMA score was 2.33 ± 0.72, and the mean GQS was 2.00 ± 0.40. Most of the videos (52.6%) were uploaded by independent medical professionals, and videos uploaded by professionals had the shortest duration and time online (P < 0.001). The source of the video was associated with numbers of “likes'', “comments'', and “shares'' for JAMA scores (P < 0.001), but there was no correlation with DISCERN scores. Generally, videos on TikTok with the shortest duration received the most numbers of “likes'', “comments'', and “shares'', but the overall quality of videos on Weibo was higher. Conclusion: Although the majority of the videos were uploaded by independent medical professionals, the overall quality appeared to be poor. Therefore, more efforts and actions should be taken to improve the quality of videos related to gestational diabetes mellitus.